Protective effect of ?-3 fatty acids in a rat focal cerebral ischemia-reperfusion model - Kavakli, Ahmet; Kose, Evren; Kus, Ilter; Zararsiz, Ismail; Akpolat, Nusret; Sarsilmaz, Mustafa (Riyadh Armed Forces Hospital, 2007)
Objective: To investigate possible neuroprotective effects of dietary supplementation of fish oil in brain ischemia-reperfusion (I/R). Methods: This investigation took place In the Experimental Research Unit, Firat University, Elazig, Turkey, from January-February 2006. The study was carried out on 12 male Wistar rats; divided into 2 groups: I/R (control) and I/R + omega-3 essential fatty acids (EFA) (experiment). The rats in the I/R group received only ordinary rat food before middle cerebral artery (MCA) occlusion. The I/R + omega-3 EFA group received omega-3 fatty acid daily via intragastric gavage (300 mg/kg Marincap capsule) with normal food before MCA occlusion for 30 days. Structural alterations in the brain tissues were semi-quantitatively analyzed (0: absent, +: Slight, ++: moderate, +++: severe). Results: There was evident severe (+++) edema, vacuolization, and eosinophilic degeneration in the I/R group, while only slight (+) edema and eosinophilic degeneration in the I/R + omega-3 EFA group in which no vacuolization was determined. These findings are consistent with the available studies in this field. Conclusion: Results from this study indicate the beneficial effects of omega-3 EFA supplementation in prevention of I/R induced damage in rats.
Keywords: Polyunsaturated Fatty-Acids; Copper/Zinc-Superoxide-Dismutase; Docosahexaenoic Acid; Dietary Supplementation; Brain; Inhibition; Gerbils; Damage